Non-modifiable Factors of Coronary Artery Stenosis in Late Onset Patients with Coronary Artery Disease in Southern Iranian Population - Seyeed Mohammad Bager Tabei; Sara Senemar; Babak Saffari; Zeinab Ahmadi; Somayeh Haqparast (Journal of Cardiovascular and Thoracic Research, 2014)
Introduction: Coronary Artery disease (CAD) is influenced by genetic factors, environment and culture behavior. The aim of the present study was to evaluate some non-modifiable risk factors of coronary heart disease such as sex, age, family history and consanguineous marriage. Methods: This is a case-control study. The study population consisted of 200 fifteen or more years old. Data were collected on 200 patients with positive angiography and 200 control subjects with negative angiography. Positive angiography was defined as coronary diameter cut greater than 50%. Statistical analysis was conducted using SPSS 11.5. In this study, data were collected through a checklist. Logistic regression and stratification were used to determine the impact of age, gender, family history, and consanguinity on the risk of stenosis. Results: The percentage of men in patients and controls were 89% and 29%, respectively. As to gender, a significant association was found between patients and controls of CAD (CI 95%, 4.014-10.052, OR 6.352). Gender was determined as a risk factor for CAD. Family history of myocardial infarction did not show a significant effect on the artery stenosis. As to consanguinity of the parents, there was no significant association between patients and controls of CAD (P> 0.05). Conclusion: These researches show that ageing increases the risk of coronary heart stenosis; also, females are more than men protected against this disease. The impact of family history of myocardial infarction and consanguineous marriage were not associated with of CAD.